Smart phone demand: An empirical study on the relationships between phone handset, Internet access and mobile services. Issue 1 (February 2015) - Hsiao, Ming-Hsiung; Chen, Liang-Chun
Highlights We explored smart phone demand by emphasizing differences between three dimensions. The three demand dimensions cover handset, mobile network and mobile services. We found demand for mobile services have weak relationship with handset and mobile network. We found significant effect of demographic variables on the demand for mobile network.